An Analysis of the Effects of Shift Work on the Lives of Married Employees - James, Fabian Andrew; Sudha, S. (Prabandhan: Indian Journal of Management, 2015)
The article focused on the lives of married employees working in shift work across the ITES companies located in Chennai. A huge number of married employees have taken up shift work these days to meet the demanding requirements in the current scenario. The number of employees working in the ITES has been expanding every year. Married employees are taking up night shifts and other shift work to become financially stable as well as to lead a luxurious life. The article studied the problems faced by the married employees in fulfilling their marital commitments. This article is an empirical paper which used multiple regression models to find the correlation between shift work and its effect on family life, marital stability, and development of children, their academic performance, and cognitive skills. Data from 200 respondents were collected from employees who were working in shift work in ITES around Chennai. The study clearly portrayed that working non-day shifts eroded the marital relationship of the couples and lowered the marital quality. The working conditions were studied, and it was found that non-day jobs significantly affected the marital stability of the couples. The study also found working in rotating schedules had a greater effect on couples with children.